Formalno-prawna problematyka archeologii współczesności w Polsce - Grajewski, Adam (Acta Universitatis Lodziensis. Folia Archaeologica, 2018)
Recently, in the circle of archaeologists, we observe discussions on the issues related to the contemporary archeology. This topic is also the subject of disputes between the opponents and the supporters of an innovative look at archeology. Studying this issue, it is worth pointing that the places and events connected with the contemporary history are increasingly becoming a subject of interest to archaeologists. It overlaps with another issue – devastation and destruction of archaeological sites along with many places of battlefields in our country. It is increasingly evident that the field of action of archaeologists touches the dark period of operation in our country by the German occupation authorities and the post-war communist authorities. We should keep in mind that even the dark part of our history must be protected. It is also our heritage, which should be a subject of protection enshrined in the Constitution of the Polish Republic with its tangible and intangible elements and without any restrictions. It would be advisable that the archaeologists, conservation authorities and all stakeholders should explain all the emerging doubts while working out on the common position in this matter. We should realize that the contemporary archeology is not only traces of the past events that surround us, but it is also the material evidence of our existence that will remain after us. It seems that the contemporary archeology is nothing but a continuation of the archeology, which evolves and follows the mankind, along with our sometimes complicated existence. It is still archeology, which is called the contemporary archeology in order to precisely define the period of its interest. We should keep in mind that the contemporary archeology is also an important element shaping the cultural awareness which further increases its value.